TRANSFORMATION OF CLINICAL DATA CLUSTERS AT THE STAGE OF INITIAL DIAGNOSIS - A. I. Mitsiukhn; E. N. Maisenia (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A clustering method of biomedical data, which allows to increase the efficiency of the primary diagnosis is considered. Diagnostic process is realized on the basis of diagnostic signs recognition methodology. Simplification of the recognition process is performed by converting the space of initial clusters. It is shown a computational algorithm of clustering and classification characteristics.